Implementasi Model Bisnis Syariah dalam Pengembangan Tanah Kavling Tanpa Riba: Studi Kasus pada PT Rezky Syariah Abadi - Muhammad Al-Jazary; Muhammad Rifki; Dwi Fathu Maharani; Aspira Delina (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study aims to analyze the implementation of the sharia business model in the development of interest-free land plots at PT Rezky Syariah Abadi, a sharia-based property developer that applies the principles of No Riba, No Penalty, No Seizure, and No Gharar throughout its transactional processes. Using a descriptive qualitative approach, data were collected through in-depth interviews with management and consumers, direct observation of operational practices, and document analysis of contracts and company policies. The findings indicate that PT Rezky Syariah Abadi consistently applies sharia principles, particularly through the use of transparent ba’i (sale) contracts, fixed-price installment schemes without interest, and a humanistic approach in addressing payment delays through negotiation and rescheduling rather than penalties. This implementation aligns with the rules of fiqh muamalah and the objectives of sharia (maqasid al-shariah), especially in terms of justice, welfare, and the protection of consumer assets. However, challenges remain, including low public literacy regarding sharia-compliant property concepts and the absence of specific government regulations governing non-bank sharia developers. Therefore, enhancing consumer education and strengthening human resource capacity are essential to maintaining the quality and sustainability of the sharia business model. This study contributes theoretically to contemporary sharia business model literature and offers a practical framework for sustainable and ethically grounded sharia-based property development.